Seismic Hazard Assessment in Machine Foundation Design: A Review Study - Noman Bilal Jabbar; Albuaoda Bushra S. (E3S Web of Conferences, 2023)
This paper presents a comprehensive review of seismic hazard assessment in machine foundation design and highlights key research directions for future studies. The review includes a detailed analysis of existing literature, that covers a wide range of subjects associated with seismic analysis and design of machine foundations. It begins with an overview of the seismic hazard assessment evaluation procedure and the various factors that influence it, such as soil properties, machine stiffness, and earthquake excitation. Then it discusses the key challenges associated with the design and seismic analysis of machine foundations, including the impact of dynamic loads and soil-structure interaction. Following the analysis of the current research, the paper identifies several important research directions for future studies. These include the development of more accurate seismic hazard assessment methodologies, using sophisticated numerical modeling methods. The paper also emphasizes the need for more comprehensive experimental studies to validate the numerical models and better understand the behavior of machine foundations under seismic loads. In brief, the paper provides a comprehensive review of the current state of knowledge in seismic hazard assessment in machine foundation design and highlights the importance of future research to proceed in this field.